If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 2(1 + 5n) = 65 3 + (1 * 2 + 5n * 2) = 65 3 + (2 + 10n) = 65 Combine like terms: 3 + 2 = 5 5 + 10n = 65 Solving 5 + 10n = 65 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 10n = 65 + -5 Combine like terms: 5 + -5 = 0 0 + 10n = 65 + -5 10n = 65 + -5 Combine like terms: 65 + -5 = 60 10n = 60 Divide each side by '10'. n = 6 Simplifying n = 6
| 7.2(x-3.75)=-28.8 | | 6x-44*4x=22 | | 8x-2x+4=8 | | 5+2.50g=2.75 | | 12+48x+36y=528 | | 2x+2(0.25x)=5 | | 6v+3(-2v+5)=69 | | 6x-44*4x= | | 8-3x+7x-23= | | 3x+4.2=2q | | 13/4=x/12 | | 28x-35y=10 | | 52-x^2=10x | | (3/4)x-21/4 | | 2-5i/4-3i | | 38+4n=45.5+2.5n | | 7(5p-2)= | | 38*4n=45.5*2.5n | | 3(0.7z+2.8)=7(1.5z+7.2) | | x^2+2x^2=576 | | 6=4y+3 | | 5-1.6x=7.4 | | -2y-10=-2 | | 51x-y=41 | | X/51=3/17 | | 2b+5b-2=12 | | -1-3x+10x-6-1= | | P-3(p-4)=2+2(p+5) | | 52-x^2+10x=0 | | X-1/3y=6 | | 2x+6=7y+7 | | 16+x*2=-56 |